Relation of size of seminal vesicles on ultrasound to premature ejaculation - Hong, Zhi-Wei (Asian J Androl, 2017)
Myriad biological factors have been proposed to explain premature ejaculation (PE). However, data correlating PE with seminal vesicles (SVs) are sparse. The study aimed to evaluate the relationship between the size of SV and PE. The cross-sectional study included 44 outpatients with PE and 44 volunteers without PE, and the size of SV was compared. Self-estimated intravaginal ejaculatory latency time, the Premature Ejaculation Diagnostic Tool (PEDT), the International Index of Erectile Function-15, and the National Institutes of Health-Chronic Prostatitis Symptom Index were used for assessment of symptoms. Compared to the control group, the PE group had significantly higher mean anterior-posterior diameter (APD) of SV (P < 0.001). The optimal mean APD of SV cutoff level was 9.25 mm for PE. In the PE group, PEDT was also higher with a mean APD of SV ≥9.25 mm compared with mean APD of SV <9.25 mm. PEDT was significantly correlated with the mean APD of SV (r = 0.326, P = 0.031). The seminal plasma proteins were compared between six PE and six matched control cases by mass spectrometry and it was shown that 102 proteins were at least 1.5-fold up- or down-regulated. Among them, GGT1, LAMC1, and APP were significantly higher in the PE group. These results indicated that men with a larger mean APD of SV might have a higher PEDT score. Transrectal ultrasound of SV should be considered in the evaluation of patients with premature ejaculation. SV might be a potential target for the treatment of patients with PE and ultrasound change in SV.